2018
DOI: 10.3389/fpsyg.2018.00861
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Resolving Failures in Human-Robot Interaction: Literature Review and Model Development

Abstract: While substantial effort has been invested in making robots more reliable, experience demonstrates that robots operating in unstructured environments are often challenged by frequent failures. Despite this, robots have not yet reached a level of design that allows effective management of faulty or unexpected behavior by untrained users. To understand why this may be the case, an in-depth literature review was done to explore when people perceive and resolve robot failures, how robots communicate failure, how f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(150 citation statements)
references
References 190 publications
5
125
0
1
Order By: Relevance
“…opportunities for children to differentiate between social vs. technical issues, making it futile to discuss these differences from an interaction perspective. Our findings resonate with an earlier literature review on failure in HRI (Honig and Oron-Gilad, 2018). Indeed, all sources of trouble identified in the current study have been observed in HRI before, albeit with the obvious contextual variations.…”
Section: Discussionsupporting
confidence: 93%
“…opportunities for children to differentiate between social vs. technical issues, making it futile to discuss these differences from an interaction perspective. Our findings resonate with an earlier literature review on failure in HRI (Honig and Oron-Gilad, 2018). Indeed, all sources of trouble identified in the current study have been observed in HRI before, albeit with the obvious contextual variations.…”
Section: Discussionsupporting
confidence: 93%
“…Mitigation of User Failures. Our discussions identified the category of intentional and unintentional User Failures as up-to-now understudied with respect to mitigation strategies [41]. Mainly how robots could react if people intentionally cause errors, e.g.…”
Section: Future Workmentioning
confidence: 99%
“…Regarding perceived competence, Honig and Oron-Gilad [49] showed that an erroneous anthropomorphic avatar lowers the customer's trust and the service encounter satisfaction. Moreover, their willingness to use the service again and to purchase goods depends on the recovery strategies: a compensation strategy is more efficient in improving the service encounter satisfaction, while the option or apology strategies are better at increasing willingness to use the service again.…”
Section: Downstream Consequences Of Interactions With Chatbotsmentioning
confidence: 99%